TINJAUAN YURIDIS MENGENAI REMISI BAGI NARAPIDANA TINDAK PIDANA KORUPSI YANG DITETAPKAN DALAM PERATURAN PEMERINTAH NOMOR 99 TAHUN 2012 (STUDI DI LEMBAGA PEMASYARAKATAN KELAS IA MEDAN) - Berutu, Debby Pristy; Kalo, Syafruddin; Ablisar, Madiasa; Hamdan, M. (Law Jurnal, 2023)
Remission for prisoners is the right of inmates, which sometimes reaps the pros and cons when the award is assessed against perpetrators of corruption. In improving remission services, Government Regulation No. 99 of 2012 concerning the second amendment to Government Regulation No. 32 of 1999 concerning Conditions and Procedures for the Rights of Residents in Community Development is considered better than previous Government Regulations. The granting of remission to corrupt convicts must meet the requirements of being willing to cooperate with law enforcement in assisting law enforcement in criminal acts of corruption to achieve the legal goal of deterring the effect on criminals. This research is normative juridical legal research combined with empirical research, which means the problem analysis process has an approach to synchronising secondary legal materials and primary data obtained from the field. The results of the study concluded that convicts of criminal acts of corruption in Class I Prison in Medan, to fulfil the requirements for granting remissions, must meet the needs as per the special provisions of statutory regulations, one of which is to perform as a Justice Collaborator witness, which in cases of criminal corruption is quite challenging to fulfil.